A Systematic Literature Review on Defense Techniques Against Routing Attacks in Internet of Things - Lanka Chris Sejaphala; Vusimuzi Malele; Francis Lugayizi (Latin-American Journal of Computing, 2025)
The proliferation of the Internet of Things (IoT) has attracted different sectors such as agriculture, manufacturing, smart cities, transportation, etc. to adopt these technologies. Most IoT networks utilize Routing Protocol for Low Power and Lossy Networks (RPL) to exchange control and data packets across the network. However, RPL is susceptible to routing attacks such as rank attacks, DIS-flooding, etc. In recent years different defense techniques have been proposed to act against these attacks i.e., Secure-Protocol, conventional Intrusion Detection Systems (IDS), and Machine Learning (ML)-based. This systematic literature review explores 39 published papers in the domain of defense techniques against routing attacks in RPL-based IoT. We review. The findings of this study suggest that most Secure-Protocol can detect and mitigate routing attacks utilizing distributed placement, ML-based can detect most attacks but lack mitigation mechanisms, and conventional IDS technique utilizes a hybrid approach in detection and placement strategies. Additionally, this study reveals that India publishes more research papers in ML-based and Secure-Protocol. Furthermore, flooding attacks are the most discussed attacks in the selected studies. Finally, Cooja Contiki is the most used simulation tool.